2014
DOI: 10.1007/s00005-014-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diethylcarbamazine Citrate and Setaria equina Excretory–Secretory Material on Rat Hepatocellular Carcinoma

Abstract: Diethylcarbamazine citrate (DEC) has been known for its efficacy to eradicate bancroftian filariasis in Egypt and other countries in the world. One of the known effects was to decrease the level of circulating filarial antigen in the patient's serum. The target of this study was to examine the effect of DEC, excretory-secretory (ES) material from the filarial parasite Setaria equina or a combination of both on the status of oxidative stress and pathogenesis of rat hepatocellular carcinoma (HCC) induced by diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Previously, repeated doses of SeqES in experimentally induced hepatocarcinogenesis could show some of the protective effects as a result of reduced inflammatory responses and oxidative stress . One of those anti‐inflammatory effects was the inhibition of complement activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, repeated doses of SeqES in experimentally induced hepatocarcinogenesis could show some of the protective effects as a result of reduced inflammatory responses and oxidative stress . One of those anti‐inflammatory effects was the inhibition of complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory properties of ES products could be applied for protection against inflammatory diseases like rheumatoid arthritis . Our previous studies for the SeqES immunomodulatory effect indicated downregulation of macrophage activity, IFN‐γ production by peripheral blood mononuclear cells (PBMCs) and complement activation (CH 50 ) . This, in turn, indicated the existence of complement‐binding or inhibitory protein.…”
Section: Introductionmentioning
confidence: 99%